Football data processing model in context of Russian national team participation in 2018 World Cup - Mikhryakov, S. V.; Naboichenko, E. S.; Polozov, A. A.; Bozhko, E. M. (Theory and Practice of Physical Culture, 2018)
The Russian national football team is presently ranked number 60-65 in the FIFA Coca Cola and www.ra-first.ru rankings. The team still faces problems of the individual player`s performance ratings and national team formation that have always been critical since 1960ies and are still addressed in statistics of the individual technical and tactical actions. The statistics, however, still shows poor if any correlation with the actual team competitive performance; and the above problems are still most effectively solved by the expert/ coach assessments. The football data processing model (DPM) we analyze and offer hereiun is more efficient than the traditional discretional decision-making models for it takes full advantage of the IT technology application in the modern sport design and management process.